New antibody-drug conjugates (ADCs) in breast cancer-an overview of ADCs recently approved and in later stages of development - Kira-Lee Koster; Jens Huober; Markus Joerger (Open Exploration Publishing Inc., 2022)
Antibody-drug conjugates (ADCs) have changed the treatment of breast cancer (BC) in more recent years. BC is a heterogenous group of malignancies with a broad range of histopathological characteristics. ADCs represent a class of therapeutics that combines an antigen-specific antibody backbone bound to a potent cytotoxic agent (the payload), via a linker, contributing to an improved therapeutic index. Currently, three ADCs received approval by the US Food and Drug Administration (FDA) and are in routine clinical use in different treatment settings; many more ADCs are in earlier and later stages of development, and their future approval will improve treatment options for patients with advanced but potentially also early-stage BC over time. Just recently, the results of three phase 3 trials (ASCENT, TULIP, and DESTINY-Breast03) evaluating sacituzumab govitecan (SG), trastuzumab duocarmazine, and trastuzumab deruxtecan (T-DXd) in different treatment settings were presented and showed promising results. This overview focuses on the newer ADCs, including T-DXd and SG, their pharmacology, mechanisms of action, and relevant studies. In addition, the latest results from trials investigating some newer ADCs, in further stages of development are presented.